THE EFFECTS OF PROGRAMMED WORK ON THE DEVELOPMENT OF SPECIFIC MOTOR SKILLS IN YOUNG FOOTBALL PLAYERS - Emin Mujezinović,; Alen Kapidžić,; Melika Muratović,; Edin Užičanin,; Fuad Babajić, (Sport Scientific And Practical Aspects, 2025)
The goal of this research was to determine the effects of programmed work on the development of specific motor skills in young soccer players. The sample of subjects in this research were football players aged 11 and 12 and they were divided into two equal groups of 30 entities. All participants are involved in the regular training process in their football clubs. The research problem was to determine whether there are positive effects of programmed work on the development of specific motor skills. A total of 6 variables from the area of specific motor skills were used in the research. The experimental work program was carried out over a period of three months and included 38 training units. After initial testing and successfully implemented programmed work and final testing, a significant impact of programmed work on the development of specific motor skills was determined. Specific motor skills that were evaluated on 6 variables in the experimental group showed a significant difference on 4 variables.